GAMBARAN PENGETAHUAN TENTANG PENGGUNAAN GIGI TIRUAN SEBAGIAN LEPASAN TERHADAP KONDISI GIGI DAN MULUT PADA MASYARAKAT DUSUN JAWA DESA KAMPUNG DALAM RANTAU PRAPAT - Ngena Ria (Poltekkes Kemenkes Medan, 2017)
Artificial teeth are used to substitute the lost teeth. Removable artificial teeth are favored by people since they are relatively inexpensive, can be removed, and worn by the owner. The cleanliness of removable artificial teeth should be taken care of; otherwise, they will contain debris and calculus which can damage oral cavity. The research used descriptive method which was aimed to find out the knowledge of using removable artificial teeth toward dental and mouth condition in the people of Dusun Jawa, Kampung Dalam Village, Rantau Prapat. The data were gathered by distributing questionnaires and directly examining oral cavities. The samples consisted of 30 people. The result of the research showed that 20 respondents (66.67%) were in good criteria in their knowledge of using removable artificial teeth, and 17 respondents (56.67%) were in moderate criteria in their knowledge of dental and mouth condition, and in dental condition, the number of DMF-T was 361 with the mean DMF-t of 12. It is recommended that people clean their removable artificial teeth at least twice a day, after breakfast before going to bed and soak them in clean water during the night. Teeth should be extracted if there is indication that they have to extracted, change them with artificial teeth, keep them and mouth hygienic to forestall dental damage.